Tegument Glycoproteins and Cathepsins of Newly Excysted Juvenile Fasciola hepatica Carry Mannosidic and Paucimannosidic N-glycans. - Andres Garcia-Campos; Alessandra Ravidà; D Linh Nguyen; Krystyna Cwiklinski; John P Dalton; Cornelis H Hokke; Sandra O'Neill; Grace Mulcahy (Public Library of Science (PLoS), 2016)
Recently, the prevalence of Fasciola hepatica in some areas has increased considerably and the availability of a vaccine to protect livestock from infection would represent a major advance in tools available for controlling this disease. To date, most vaccine-target discovery research on this parasite has concentrated on proteomic and transcriptomic approaches whereas little work has been carried out on glycosylation. As the F. hepatica tegument (Teg) may contain glycans potentially relevant to vaccine development and the Newly Excysted Juvenile (NEJ) is the first lifecycle stage in contact with the definitive host, our work has focused on assessing the glycosylation of the NEJTeg and identifying the NEJTeg glycoprotein repertoire. After in vitro excystation, NEJ were fixed and NEJTeg was extracted. Matrix-assisted laser desorption ionisation-time of flight-mass spectrometry (MALDI-TOF-MS) analysis of released N-glycans revealed that oligomannose and core-fucosylated truncated N-glycans were the most dominant glycan types. By lectin binding studies these glycans were identified mainly on the NEJ surface, together with the oral and ventral suckers. NEJTeg glycoproteins were affinity purified after targeted biotinylation of the glycans and identified using liquid chromatography and tandem mass spectrometry (LC-MS/MS). From the total set of proteins previously identified in NEJTeg, eighteen were also detected in the glycosylated fraction, including the F. hepatica Cathepsin B3 (FhCB3) and two of the Cathepsin L3 (FhCL3) proteins, among others. To confirm glycosylation of cathepsins, analysis at the glycopeptide level by LC-ESI-ion-trap-MS/MS with collision-induced dissociation (CID) and electron-transfer dissociation (ETD) was carried out. We established that cathepsin B1 (FhCB1) on position N80, and FhCL3 (BN1106_s10139B000014, scaffold10139) on position N153, carry unusual paucimannosidic Man2GlcNAc2 glycans. To our knowledge, this is the first description of F. hepatica NEJ glycosylation and the first report of N-glycosylation of F. hepatica cathepsins. The significance of these findings for immunological studies and vaccine development is discussed.